Psikoedukasi Pada Pasien Diabetes Mellitus di Wilayah Kerja Puskesmas Magelang Utara Kota Magelang - Isworo, Adi; Suharsono, Suharsono; Susanto, Abiyyu Naufal (Penerbit Widina, Widina Media Utama, 2024)
Psychoeducation for cadres, families and diabetes mellitus patients in North Kramat Village, North Magelang District, Magelang City is needed as a promotive and preventive effort for non-communicable disease programs. Community participation through empowering health cadres in optimizing reducing the level of family burden, strengthening family support, regularity in measuring glucose levels, and adherence to medication and diet. This service aims to determine the practice of implementing health cadre empowerment in screening and efforts to optimize cadres in families with diabetes mellitus patients. The methode used is structured counseling, focus group discussions. The activities were carried out for one year, carried out in North Kramat Village, North Magelang District, Magelang City, the working area of the North Magelang Community Health Center. Empowerment is observed by community health center nurses and health cadres during early detection of glucose levels, compliance with taking medication and diet. The results of empowerment in providing psychoeducation to families with diabetes mellitus patients showed that the average practice assessment result was an increase of 79,23 (79,23%) from the previous 70,8 (70,8%) and there was an increase 8,43%. Through empowerment we can increase optimization in screening for families and diabetes mellitus patients. Greater outreach of screening to the community. Extensive and supports the performance of community health center services to carry out non-communicable disease programsABSTRAKPsikoedukasi pada kader, keluarga serta pasien diabetes melitus di Kelurahan Kramat Utara, Kecamatan Magelang Utara, Kota Magelang diperlukan sebagai upaya promotif dan preventif program penyakit tidak menular. Partisipasi masyarakat melalui pemberdayaan kader kesehatan dalam mengoptimalkan penurunan tingkat beban keluarga, menguatkan dukungan keluarga, keteraturan dalam mengukur kadar glukosa, dan kepatuhan minum obat dan diet. Pengabdian ini bertujuan untuk mengetahui praktik pelaksanaan pemberdayaan kader kesehatan dalam skrining dan upaya optimalisasi kader pada keluarga dengan pasien diabetes melitus. Metode yang digunakan berupa penyuluhan terstruktur, fokus group discussion. Pelaksanaan kegiatan selama satu tahun, dilaksanakan di Kelurahan Kramat Utara, Kecamatan Magelang Utara, Kota Magelang wilayah kerja Puskesmas Magelang Utara. Pemberdayaan diobservasi oleh perawat puskesmas dan kader kesehatan saat deteksi dini kadar glukosa, kepatuhan minum obat dan diet. Hasil pemberdayaan dalam memberi edukasi psikoedukasi pada keluarga dengan pasien diabetes melitus didapatkan hasil rata-rata penilaian praktik adalah 79,23 (79,23%) dari yang sebelumnya 70,8 (70,8%) dan terdapat kenaikan 8,43%. Melalui pemberdayaan maka dapat meningkatkan optimalisasi dalam skrining kepada keluarga dan pasien diabetes melitus. Jangkauan skrining ke masyarakat lebih luas dan mendukung kinerja layanan puskesmas untuk menjalankan program penyakit tak menular.